Rare Presentation of Metastatic Prostate Adenocarcinoma as a Meningioma Mimic - Rahmathulla, Gazanfar; Prayson, Richard A.; Weil, Robert J. (Journal of Neurological Surgery Reports, 2014)
Background Dural lesions in the anterior skull base may occur secondary to benign or malignant pathology that may be difficult to differentiate on imaging. Detailed clinical evaluation in many cases will narrow the differential diagnosis. In spite of using all the available information, in certain cases the underlying etiology of a lesion remains unclear.Participant We report a rare case of metastatic prostate adenocarcinoma to a meningioma in a 67-year-old-man who presented with progressive confusion and mental status alterations with no prior history of malignancy. Neuroimaging revealed a large anterior skull base lesion.Results The lesion was surgically resected, and histopathology revealed a collision tumor, in which prostate adenocarcinoma was found admixed with a World Health Organization grade I meningioma.Conclusion Anterior dural skull base lesions can be either benign or malignant. Although infrequently reported, a benign-appearing dural-based lesion may be a manifestation of an underlying malignancy, and a thorough clinical, radiologic, and pathologic examination may be necessary, especially in the elderly.
Keywords: collision tumor; anterior skull base; meningioma; prostate cancer